Developing an educational app for students with autism - Somerton, Michelle (Frontiers in Education, 2022)
This paper describes the design, development, and pilot test of an App, and explains how research based strategies and pedagogical approaches can be embedded within an App based format. The aims and scope of the research were to; (a) synthesize research findings on reading comprehension difficulties for students with autism spectrum disorder (ASD) identifying evidence-based strategies that underpin improvements; (b) determine the features associated with the design of ‘quality’ educational apps; (c) create a reading comprehension app for students with ASD and; (d) test in applied settings. The study utilized extensive literature searches to determine key considerations for design and development of the App and then piloted the completed product through employing an AB case study design with two participants. Pre and post testing measured discrete vocabulary skills including expressive and receptive vocabulary, reading comprehension, phonological development, and reading behaviors. The results of the design process and pilot test provide recommendations for developers and educators when considering the critical pedagogical content and functionality of Apps for supporting reading comprehension skills for students with Autism.